Composition of raw and lyophilised free-range chicken egg using proximate analysis - Yunus, Nur Aqillah; Sharifuddin, Nur'ain; Sukor, Rashidah (Universiti Putra Malaysia, 2024)
This study examined the proximate composition of free-range chicken eggs in two preparation methods, which were raw and lyophilisation. Eggs were separated into albumen and yolk, and then analysed in both raw and lyophilised states. Freeze drying was performed by initially freezing at -10°C, followed by lyophilisation at -47°C for 72 hours. The proximate analysis was conducted according to AOAC (2016) standards to determine moisture, ash, crude protein, and crude fat contents. Moisture content varied significantly (p<0.05) between raw and lyophilised samples of albumen while no significant difference (p>0.05) was found between yolk samples of different conditions. All samples showed lower ash content but higher protein and fat levels for freeze-dried samples, indicating changes in the concentration of these macronutrients post-moisture removal. Ash and crude protein contents differed significantly (p<0.05) between raw and lyophilised yolk and albumen samples. However, for crude fat, only yolk samples presented a distinct difference (p<0.05) when comparing the raw and lyophilised conditions. Compositions of the egg differed when a processing method was applied as opposed to its raw form.